The Optimisation of Technological Parameters of Centrifugal Impact Crushers for Grain Grinding - Natalya Kamysheva; Ayap Kurmanov; Vladimir Sapa; Serik Akhanov (Journal of Applied Engineering and Technological Science (JAETS), 2026)
This study aims to increase the energy efficiency and product uniformity of centrifugal impact crushers for feed grain processing through targeted optimisation of technological parameters. A direct-impact mechanism was implemented by profiling the stationary impact lining with an involute tooth geometry that ensures grain collisions at a 90° angle, minimising kinetic energy losses. Experimental tests were conducted on pea grain (moisture 11.6%) using a prototype crusher developed at Kostanay Regional University. Rotor speed was set at 2000 rpm, throughput maintained at 400 kg/h. The optimised crusher achieved a specific energy consumption of 2.89 kWh/t, which is 22% lower than a conventional impact crusher of similar capacity. The crushed product had an arithmetic mean particle size of 1.31 mm with 85% of particles within the 0.5-1.5 mm range, meeting zootechnical standards. Theoretically, this work refines comminution models by quantifying the effect of impact angle on breakage efficiency and provides a design criterion (involute profile with 47°-56° contact angles) for normal-impact crushers. Practically, the prototype offers a low-energy, high-uniformity solution suitable for feed mills and can be retrofitted into existing machines. The main contribution is the experimental validation that deliberate alignment of impact geometry reduces specific energy by over one-fifth without sacrificing throughput or quality, opening a new direction for energy-efficient grinder design.